Diversity of entomofauna associated with greenhouse-grown tomatoes in Algiers (North Algeria) - Fatiha DJEBARA; Abdelmadjid BENZAHRA; Fateh MIMECHE; Lounes SAHARAOUI (Studia Universitatis Babeș-Bolyai. Biologia, 2018)
Tomato is an important economic crop worldwide. Many insect pests are cause both quality and quantity yearly decrease on greenhouse-grown tomatoes. Thus, diversity and relative abundance of both harmful and useful insects were investigated in greenhouse-grown tomatoes in Algiers coastal area. The inventory was realized in 2014 by using yellow sticky platelets traps. The information obtained allowed us to elaborate an inventory with no less than 1449 individuals belonging to 46 different taxons, distributed among eight orders and 26 families. Useful entomofauna is very rich and represented around 32% of the total population with five predators and a dozen of Hymenoptera parasites. Presence ofa significant predatory parasite complex may contribute to the regulation of pests in tomatoes greenhouse and carry out control programs against the main harmful pest of this crop. This assessment of the entomofauna will make it possible to carry out control programs against the main pests of this culture. The results of this study will contribute to finding mechanisms and conditions for reducing the negative impacts of the bio-aggressors of tomato.